Understanding Freedom. Reason or Passions? - Biegalska, Agnieszka (Filozofia Chrześcijańska, 2013)
What does human ability to take decisions depend on? Reason or passions? What mechanism governs the process of shaping our beliefs? Why do we consider a given opinion credible? All these questions are familiar to anyone who even once pondered on the phenomenon of human freedom – a phenomenon whose existence is commonly believed to be obvious. The article is yet another attempt to address the above questions. The presented reflections will be set against the background of the thought of William James.